PISA 2009 at a glance (Paris, 2010)
"PISA 2009 at a Glance is a companion publication to PISA 2009 Results, the six-volume report on the 2009 survey conducted by the OECD’s Programme for International Student Assessment (PISA). PISA assesses the extent to which students near the end of compulsory education have acquired some of the knowledge and skills that are essential for full participation in modern societies. Its triennial assessments of 15-year-olds focus on reading, mathematics and science.